Regular White People Things: The Presence of White Fragility in Interracial Families. Issue 4 (21st May 2021) - Robinson‐Wood, Tracy; Muse, Chantal; Hewett, Ruthann; Balogun‐Mwangi, Oyenike; Elrahman, Jaylan; Nordling, Ava; Abdulkerim, Noora; Matsumoto, Atsushi
Abstract : Objective: To better understand how biracial/multiracial millennials make meaning of their multiple identities and racial socialization messages within their interracial families. Background: A small body of research suggests that the content of parents' race messages to their biracial/multiracial children may have profound social and psychological ramifications. Changing American demographics, including the growth of biracial/multiracial populations, have created a demand for careful examination of this group's racialized experiences. Method: To examine the racial socialization experiences of biracial/multiracial participants ( n  = 30), this qualitative substudy used thematic analysis, an intersectional theoretical framework, and a phenomenological approach in analyzing open‐ended responses. Results: We found that interracial families employed a number of racial socialization messages, including those that extol mainstream cultural values as well as communications that fuel race‐related stress and identity politics. Conclusion: Findings highlight the prevalence of dominant Western cultural values and racial silence in the socialization messages within interracial families and the reality of racism and racial awareness among individuals identifying as biracial/multiracial. Implications: The findings in this study suggest a need to examine racial socialization as a function of parents' salient identities, including gender, race, and immigration status.